2019
DOI: 10.29399/npa.23609
|View full text |Cite
|
Sign up to set email alerts
|

Tendency towards Eating Disorders and associated sex-specific risk factors among university students

Abstract: Introduction: Eating disorders have frequently been reported among young adults including university students. Detailed information on the prevalence and associated gender-specific determinants of eating disorders are lacking, particularly among students in the north western region of Pakistan. The current cross-sectional study was designed to fill this gap in the literature. Methods: Total of 672 students (female: 56%, age range: 18-26 years) were enrolled and data collected between October 2016 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…Contrary to our study, in a study conducted on university students, it was found that male students have more eating attitude disorders than females [37]. According to Din et al, no significant difference was found between male and female students in terms of eating attitudes [38]. Similarly, in a cross-sectional study conducted with nutrition and dietetics students, it was found that the incidence of deterioration in eating attitudes decreased as the undergraduate degree increased [39].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our study, in a study conducted on university students, it was found that male students have more eating attitude disorders than females [37]. According to Din et al, no significant difference was found between male and female students in terms of eating attitudes [38]. Similarly, in a cross-sectional study conducted with nutrition and dietetics students, it was found that the incidence of deterioration in eating attitudes decreased as the undergraduate degree increased [39].…”
Section: Discussioncontrasting
confidence: 99%
“…Sample Size N = 1047. ED Measures : EAT-26; SCOFF %Female = 61.3%, Age = 20.2 years, BMI = 23.3 kg/m 2 8 28 Din (2019) [ 104 ] Pakistan Cross-sectional design. Sample Size N = 672.…”
Section: Resultsmentioning
confidence: 99%
“…Eating disorders, characterized by disturbed attitudes toward eating, can become a serious health problem for adolescents and young adults. A growing body of evidence suggests that the prevalence of eating disorders and excessive weight concerns is increasing among the young population [6].…”
Section: Introductionmentioning
confidence: 99%